The Myth of Emancipation through Interaction. On the Relationship between Interactive Dimensions and Emancipating Potentials of Contemporary (Digital) Art - Philipsen, Lotte (The Nordic Journal of Aesthetics, 2012)
The purpose of this article is to critically address a widespread assumption that reads like this: Works of art that make use of digital media automatically, through interactivity, are generally better suited for generating democratic processes in society than other art forms or phenomena that do not make use of digital media, and, therefore, digital art is more avant-garde than other art forms. By analysing the chains of equivalence underlying this assumption the article presents and discusses a number of issues that, taken together, render this assumption fallacious.